(untitled) (Research, Society and Development, 2021)
Objective: To evaluate the level of dental anxiety in patients at a teaching clinic in southwestern Bahia. Material and Methods: 80 patients were approached under dental care for this study, after consent to sign the Informed Consent, with data collection performed through two questionnaires, one socioeconomic and one of anxiety assessment. All security protocols described by the current pandemic and health situation were met strictly. The collected data were tabulated in excel spreadsheet and transferred to statistical program SPSS (IBM) version 25.0. Result: The study presented 77.5% of female interviewed, 46.3% with income up to 1 basic salary and 36.1% completed high school. 31.2% of patients only visited the dentist when they felt pain, 28.7% felt uncomfortable with the anesthesia and 49% had mild anxiety. Conclusion: Anxiety is present among patients, and a way to ease this situation is through humanized dentistry, dealing with the patient in a direct and specific way.